PRE/TRE elements act as transcription activators in Drosophila S2 Cells. - Chetverina, D.A.; Mikhailova, A.V.; Georgiev, P.G.; Erokhin, M.M. (Doklady. Biochemistry and Biophysics, 2017)
The Drosophila PRE/TRE elements are DNA targets for Polycomb and Trithorax group proteins, which control repression and activation of gene transcription, respectively. In this study, we show that, in transiently transfected Drosophila S2 cells, bxdPRE activates transcription driven from different promoters. Using CG32795 gene promoter, we demonstrate that other PRE/TRE elements-Fab7, en, eve, and CycB-also act as transcription activators in this model system.